IMPLEMENTATION OF FLEXIBLE EDUCATION IN THE PERSPECTIVE OF ESSENTIALISM EDUCATION PHILOSOPHY - We’u, Gregorius; Pali, Agustina (Fakultas Ilmu Pendidikan Universitas Negeri Surabaya, 2024)
This research examines the application of essentialism education philosophy in the Indonesian education system which aims to integrate cultural values in learning. Education in Indonesia faces the challenge of creating learners who are not only academically competent but also have character based on cultural values. Essentialism, with its emphasis on the inheritance of cultural values, offers a solution to maintain cultural stability through relevant and flexible education. Using a descriptive qualitative approach, this research examines the ontological, epistemological and axiological views in essentialism and their implications in an inclusive and flexible curriculum. The results show that education should include the intellectual, emotional, social, and spiritual development of learners. In this context, essentialist education focuses on character building, activeness in learning, and strengthening learners' morality to prepare them for the challenges of life in this world and the hereafter.